Anti-Glication Activity Test of Effervescent Granules Combination of Green Okra (Abelmoschus Esculentus L) and Better Gourd (Momordica Charantial L) Fruit Extract Using UV-VIS Spectrophotometry Method - Suharyanto, Suharyanto; Harningsih, Tri; Harini, Sri (Indonesian Journal of Global Health Research, 2024)
Glycation is a non-enzymatic chemical reaction between reducing sugars and amino groups from proteins, nucleic acids or phospholipids to form advanced glycation end products (AGEs). The formation of AGEs is related to blood glucose control. Inhibition of AGEs formation in diabetes can limit tissue damage. The bad impact of increasing blood glucose levels is hyperglycemia. Bitter melon fruit empirically lowers blood glucose in test animals by reducing blood glucose levels. through the process of inhibiting gluconeogenesis in the liver, protecting pancreatic beta cells, increasing insulin sensitivity and reducing oxidative stress. Meanwhile, okra fruit contains metabolite compounds for the treatment of diabetes mellitus, through inhibiting the activity of the α-glucosidase enzyme, improving pancreatic β cells and antioxidant properties. Effervescent is something that contains gas bubbles, like water-soluble tablets with a foaming effect. The aim of this research is to determine the Anti-Glycation Combination of Effervescent Granules from Green Okra and Bitter Gourd fruit extracts. The research was carried out by extracting Bitter Gourd and Green Okra. The extraction results are mixed in the same ratio to make three Effervescent Granule formulations. The results of the Effervescent granule formulation were tested for anti-glycation activity using the spectrophotometric method. From the research results, it can be concluded that the combination formula of 200mg bitter melon extract and 200mg green okra extract has the best results with a % reduction in glycation of 52.650% ± 0.208; IC50 108.5255 ppm with %KV 0.522